MAMACARE: Aplikasi Mobile Pendukung Ibu Hamil dan Ibu Baru Berbasis Komunitas dan Layanan Kesehatan Digital - Sitorus, Michael; Aini Melati, Zuhda; Hasanah, Zahra Nisatul; Anggun Herdilanggiva, Nabila (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Maternal and newborn health is a critical factor in improving human resource quality in Indonesia, yet maternal and infant mortality rates remain significant challenges. Limitations in access to information, healthcare services, and social support affect the well-being of mothers during pregnancy and postpartum. MamaCare is a community-based mobile application integrating health education, online medical consultation, and community forums into a single platform. This application is designed to provide comprehensive support, enhance health literacy, and strengthen social networks for pregnant women and new mothers. Therefore, MamaCare is expected to contribute to reducing maternal and infant mortality rates and improving maternal and child healthcare quality in the digital era. This paper discusses the background, objectives, main features, and advantages of MamaCare as an innovative support solution for pregnant and new mothers.